Comparison of Fabrication Methods for Fiber‐Optic Ultrasound Transmitters Using Candle‐Soot Nanoparticles. Issue 9 (24th February 2023) - Bodian, Semyon; Aytac‐Kipergil, Esra; Zhang, Shaoyan; Lewis‐Thompson, India; Sathasivam, Sanjayan; Mathews, Sunish J.; Alles, Erwin J.; Zhang, Edward Z.; Beard, Paul C.; Gordon, Ross J.; Collier, Paul; Parkin, Ivan P.; et al.
Abstract: Candle‐soot nanoparticles (CSNPs) have shown great promise for fabricating optical ultrasound (OpUS) transmitters. They have a facile, inexpensive synthesis whilst their unique, porous structure enables a fast heat diffusion rate which aids high‐frequency ultrasound generation necessary for high‐resolution clinical imaging. These composites have demonstrated high ultrasound generation performance showing clinically relevant detail, when applied as macroscale OpUS transmitters comprising both concave and planar surfaces, however, less research has been invested into the translation of this material's technology to fabricate fiber‐optic transmitters for image guidance of minimally invasive interventions. Here, are reported two fabrication methods of nanocomposites composed of CSNPs embedded within polydimethylsiloxane (PDMS) deposited onto fiber‐optic end‐faces using two different optimized fabrication methods: "All‐in‐One" and "Direct Deposition." Both types of nanocomposite exhibit a smooth, black domed structure with a maximum dome thickness of 50 µm, broadband optical absorption (>98% between 500 and 1400 nm) and both nanocomposites generated high peak‐to‐peak ultrasound pressures (>3 MPa) and wide bandwidths (>29 MHz). Further, high‐resolution (<40 µm axial resolution) B‐mode ultrasound imaging of ex vivo lamb brain tissue demonstrating how CSNP‐PDMS OpUS transmitters can allow for high fidelity minimally invasive imaging of biological tissues is demonstrated. Abstract : This article reports on two fabrication methods of nanocomposites composed of candle‐soot nanoparticles embedded within polydimethylsiloxane deposited onto fiber‐optic end‐faces using two different optimized fabrication methods: "All‐in‐One" and "Direct Deposition." These demonstrate high‐resolution (<40 µm axial resolution) B‐mode ultrasound imaging of ex vivo lamb brain tissue.